Cash in on the coming real estate crash : - Decker, David (Wiley, 2006)
After five years of skyrocketing real estate prices, fueled by low interest rates, aggressive lenders, and relative economic prosperity, something has to give. Thanks to nonstop recent press coverage of America's overheated housing market, you are probably wary of buying your next property at the top of the market. So what should you do?Whether you're an individual investor or a homeowner, Cash In on the Coming Real Estate Crash shows you how to gauge the risk of a housing bust in your own local market. More importantly, it shows you how to hedge against a crash and position yourself to profit if the bubble bursts.